Circular Economy in the building sector : Three cases and a collaboration tool - Leising, Eline; Quist, Jaco; Bocken, Nancy (Journal of Cleaner Production, 2018)
The Circular Economy (CE) gained significant traction in business and academia. While in the building sector issues around energy efficiency are being widely explored, CE is still a relatively new topic. This article reports on three CE pilots in the Dutch building sector and develops a collaboration tool for developing and operating circular buildings and their supply chain collaborations. First, a conceptual framework is developed to study supply chain collaboration in circular buildings, which uses theoretical building blocks for visions, actor learning, network dynamics and business model innovation. Second, a case study is presented where the framework is applied to three cases using semi-structured interviews and document analysis. Third, an empirically-based tool is developed to enhance collaboration for CE in the building sector. The cases include a newly built project, a renovation project and a demolition project. It was found that developing circular buildings requires (i) a new process design where a variety of disciplines in the supply chain is integrated upfront, (ii) the co-creation of an ambitious vision, (iii) extension of responsibilities to actors along the entire building supply chain, and (iv) new business and ownership models.
Keywords: Built environment; Circular Economy; Closed loop supply chain; Industrial Ecology; Supply chain collaboration; Sustainable innovation